Electromyographic validation of the trapezius and serratus anterior muscles in rowing exercises with middle and closed grip - Büll, Marilena Longo [UNESP]; Freitas, V. [UNESP]; Vitti, M.; Rosa, G. J M [UNESP] (My University, 2003)
Because the lack of specialized textbooks on the select and indication of basic exercises for physical conditioning programmes, an electromyographic study of the trapezius (upper portion) (TS) and the serratus anterior (lower portion) (SI) muscles in rowing exercises with middle and closed grip in three different modalities, upright, sitting and bent over was performed. The tests were carried out with 24 male volunteers, 18 to 25 years old, by using a two-channel TECA TE 4 electromyograph and Hewlett Packard surface electrodes. For exercises execution, a supine bench, a straight board and a 1,20 m-long bar made of light wood were used. The results showed that TS acted preferentially with closed grip sitting and bent over modalities, and presented no difference among the grips for upright rowing. SI acted preferentially with closed grip in all modalities, however, with activity levels that do not justify its indication for physical conditioning programmes.
Keywords: adult; back muscle; conditioning; electrode; electromyogram; electromyography; exercise; hand grip; human; human experiment; male; muscle action potential; normal human; physical performance; sitting; standing; supine position; trapezius muscle; validation process; volunteer; wood; Adolescent; Adult; Back; Electromyography; Exercise; Hand Strength; Humans; Male; Muscle, Skeletal; Physical Fitness; Posture; Reference Values; Reproducibility of Results; Thorax; Upper Extremity